Kesantunan Berbahasa untuk Anak Prasekolah di kota Depok - Muzaki, Ahmad; Yayan, Sudrajat; Chadis (Presisi Jurnal Pengabdian Masyarakat, 2023)
Indonesia comes from various ethnic groups, each of which has its own unique customs, arts and culture, and language, which are sources for the growth and development of people's creativity. In people's lives there is definitely an interaction that occurs. Each society will bring its own language and culture of origin. No exception is the food that is served in every community activity. Politeness in language is very influential on human characteristics. If someone is polite in language, it will indicate that the person's personality is good. On the other hand, if someone whose personality is actually not good, even though he tries to speak properly, correctly, and politely in front of other people; one day he is unable to cover up his bad personality so that bad and impolite choices of words, expressions or sentence structures appear. So that we can see and judge someone starting from their language. Therefore, we carry out community service in language politeness for preschoolers in Meruyung Village, Limo District, Depok City